Synthesis of self-assembled micro/nano structured manganese carbonate for high performance, long lifespan asymmetric supercapacitors and investigation of atomic-level intercalation properties of OH− ions via first principle calculation. (February 2020) - Karuppaiah, M.; Akilan, R.; Sakthivel, P.; Asaithambi, S.; Shankar, R.; Yuvakkumar, R.; Hayakawa, Y.; Ravi, G.
Highlights: The electrochemical performance of MnCO3 was investigated as a function of their morphologies. The self-assembled complex grain growth of 3D MS/NCs MnCO3 was used to fabricate the superior supercapacitor electrode. The best sample of 3D MS/NCs MnCO3 / /AC ASC exhibited high energy & power densities and outstanding long cycle stability. The binding energy of OH − ions on the surface of MnCO3 is −2.81 eV. DFT study confirms weak interaction behaviour between OH − and MnCO3 . Abstract: Recent advances in the development of manganese carbonate (MnCO3 ) have opened up new attractive electrode material for supercapacitor applications. However, limited internal specific capacitance and long cycle stability of MnCO3 due to its low electrical conductivity, poor interfacial properties and simple geometric configurations need to be further improved. Development of smart micro-nano architecture for electrode materials preparation is a critical challenge nevertheless it provides high specific capacitance, rich rate capability and long cycle stability. To achieve this, the facile strategy has been adopted to synthesis self-assembled micro-nano architecture of MnCO3 via simple co-precipitation, microwave and hydrothermal-assisted methods. The proposed first principle calculation study confirmed the weak interaction behaviour between OH − and MnCO3 and tiny volume expansion of unit cell are favourable for rapid charging mechanism and high rate performance. The optimised complex grain growth of 3D MS/NCs MnCO3 electrode delivered an ultrahigh specific capacitance of 302.47 F g −1, high rate capability and long cycle stability. Moreover, an asymmetric supercapacitor is employed in as-prepared 3D MS/NCs MnCO3 as positive electrode and activated carbon as negative electrode which exhibits high specific energy of 18.07 W h kg −1, power density of 7498 W kg −1 and superior capacitance retention of 98.79% even after 10, 000 cycles. From these results, we concluded that the self-assembled micro-nano structures are preferred as the future promising electrode architecture for supercapacitors. Graphical abstract: Image, graphical abstract